2013
DOI: 10.1111/jocn.12056
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions for homeless women

Abstract: Community nursing can develop and trial programmes for homeless women including content within group sessions, counselling or advocacy within or without a therapeutic community, as presented in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 40 publications
0
36
0
16
Order By: Relevance
“…For example, in faith-based communities, nurses use advocacy to design and provide health promotion and disease prevention programs, and appropriate health services for the elderly population (McGinnis & Zoske, 2008). To reduce the risk of homelessness for women without permanent shelter, Speirs, Johnson, and Jirojwong (2013) reported that community health nurses use advocacy to develop structured education, support sessions, and therapeutic communities. They also noted that these interventions act to reduce psychological distress, improve self-esteem, and encourage the use of health care services.…”
Section: Uses Of [Chn] Advocacymentioning
confidence: 98%
See 3 more Smart Citations
“…For example, in faith-based communities, nurses use advocacy to design and provide health promotion and disease prevention programs, and appropriate health services for the elderly population (McGinnis & Zoske, 2008). To reduce the risk of homelessness for women without permanent shelter, Speirs, Johnson, and Jirojwong (2013) reported that community health nurses use advocacy to develop structured education, support sessions, and therapeutic communities. They also noted that these interventions act to reduce psychological distress, improve self-esteem, and encourage the use of health care services.…”
Section: Uses Of [Chn] Advocacymentioning
confidence: 98%
“…This attribute is most evident among vulnerable populations such as the homeless (Speirs et al, 2013), students (Ratts et al, 2007), and military families (Military One Source, 2014). Also, immigrant families need assistance and support to access health programs and resources (McElmurry et al, 2003) as well as the elderly (McGinnis & Zoske, 2008) and those living with chronic conditions such as cancer (Hagan & Donovan, 2012;Jennings-Sanders & Anderson, 2003).…”
Section: Defining Attributesmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous reviews of interventions for homeless persons have been limited to a narrative synthesis of the empirical evidence on the effectiveness of interventions for homeless people (Hwang, Tolomiczenko, Kouyoumdjian, & Garner, ), homeless women (Speirs, Johnson, & Jirojwong, ), and homeless youth (Altena, Brilleslijper‐Kater, & Wolf, ). Existing evidence to determine psychosocial interventions that can have demonstrable effects on psychosocial outcomes among homeless adults is sparse.…”
Section: Introductionmentioning
confidence: 99%